Subjectivity in a therapeutic process as a predictor of psychotherapeutic success - Joanna Dzierżanowska-Peszko; Małgorzata Artymiak (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Reflections on the uniquely human dimensions of behavior over the last few decades have become a meeting space connecting different sciences. The holistic health model emphasizes the subjectivity of man. Humans are open and active, and remain in relationships with others; they relate to the world they live in and seek meaning. Subjectivity in the psychological perspective can be described in three ways: subjectivity as identity, individuality, specific experience of self; subjectivity as the ability to initiate, regulate, direct, and realize goal-oriented and autonomous activity; subjectivity as the application of one’s own system of values. Subjectivity or causality (core features agency) expresses itself in the ability to make choices and planning, but also to directing actions and the realization of plans. The motivation to begin psychotherapy is influenced by numerous motives and conditions. Internal motivation is the main subjective resource in therapy. People internally motivated function better in better areas of life. They are characterized by greater involvement, activity, trust in their own abilities, persistence, creativity, a feeling of self-worth and general well-being. They experience engagement and immersion in the activities they undertake. The experience of causality – understood as the experience of being the author of events, the experience of having influence over events – is the fundamental cause without which the feeling of self-causality will not appear during development. As noted by R. White, it is a fundamental experience for good functioning and coping with the challenges of life, including illness.